The Development of Financial Obligation Assistance in Inter-State Relations Regarding Environmental Protection: a Review of The Paris Agreement 2015 - Azka Zuhaida; Asry M. Alkazahfa (Padjadjaran Journal of International Law, 2023)
Abstract The increasing global environmental issues affect how countries view international environmental policy. This insists countries carry out joint international responsibility on environmental law issues which later developed as Common but Differentiated Responsibility and Respective Capabilities principle (Principle of CDR-RC). The implementation of the principle should be seen as the aspect of financial assistance from developed countries to developing countries in the Paris Agreement 2015. This research aims to determine the development of the relation-interaction of the financial assistance between developed countries and developing countries in the context of international environmental law, especially regarding climate change issues as well as the obligation and financial mechanism in the Paris Agreement 2015. The result shows a development of universal responsibility into a shared international responsibility in overcoming climate change issues. Several different principles in each international instrument affect relation-interaction and financial assistance. Furthermore, the financial assistance is regulated in detail in Article 9 of the Paris Agreement 2015 with financial mechanisms referred to the United Nations Framework Convention on Climate Change (UNFCCC). Keywords: financial assistance, developed and developing countries, Paris Agreement 2015